Study on energy consumption of multi-trains tracking on long heavy down grade of high-speed railway. Issue 4 (May 2019) - Chen, Y; Guo, H G; Ai, Y P; He, H
Abstract: For the characteristics of high-speed train tracking operation on long heavy down grade of High-speed Railway, a cellular automaton dynamiccs model is proposed to simulate the energy consumption of multi-train tracking operation on long heavy down grade based on the NaSch model. Through numerical simulation, this paper studies the influence of different long slope value on the energy consumption of high-speed railway traffic flow. The simulation results show that the energy consumption model can accurately reflect the energy consumption of multi-train tracking operation on long heavy down grade. At the same time, the phenomenon of traffic waves that sometimes go and sometimes stop is reproduced. According to the simulation results, it can be concluded that the total energy consumption of multi-train tracking flow decreases gradually with the increase of slope value. The simulation results show that the energy consumption of starting, accelerating and decelerating of high-speed trains will decrease with the decrease of slope value. The results provide a scientific theoretical basis for efficient operation and energy-saving operation of high-speed railway. It has some guiding significance.